Zagłada „Domu Wasiaków”. Praktyka teorii etnopsychoanalitycznej - Żerkowski, Michał (Studia Etnologiczne i Antropologiczne, 2016)
The heretofore undescribed case of a ruined Łódź villa from the thirties of the twentieth century, known as the so-called the House of Wasiak, binding with different images, still operates in the narrative of the residents of the Marysin area, and “the House of Wasiak” itself as a link in the local discourse—an element whose meaning is conditioned by the existence of another powerful signifier—should be regarded as the key to the understanding of the mechanisms shaping the complex picture of local relations. Relations that are standard for the Polish context of social, political and urban changes today being as they are a result of a truly palimpsestic buildup of stories and traumas.